Ефективність використання матеріально-технічних ресурсів – неодмінна умова конкурентоспроможного господарювання - Збарський, В. К.; Збарский, В. К.; Zbarskyi, V.; Єременко, Денис Володимирович; Еременко, Денис Владимирович; Yeremenko, Denys (Мелітополь: ТДАТУ, 2017)
UK: В статті розглянуто особливості ресурсного забезпечення фермерських господарств як однієї із засад їхньої конкурентоспроможності. Проаналізовано характер використання земельних та трудових ресурсів в системі фермерських господарств. Обґрунтовано необхідність системного підходу щодо підвищення ефективності використання наявного ресурсного потенціалу вітчизняного фермерства. З метою здійснення оцінки ефективності використання ресурсного потенціалу в умовах конкретного регіону проаналізовано динаміку відповідних показників на прикладі сільськогосподарських підприємств Черкаської області. В рамках статті проаналізовано динаміку ресурсного потенціалу сільськогосподарських підприємств Черкаської області. EN: Based on the current state of the agricultural sector, global trends and challenges, it needs to be reformed in order to increase the competitiveness of its products both on the domestic and on world markets, which will promote the development of rural areas. The article deals with the features of resource provision of farms, as one of the bases of their competitiveness. The nature of the use of land and labor resources in farms is analyzed. The necessity of the system approach to increase the efficiency of using the available resource potential of domestic farming is substantiated. In order to evaluate the effectiveness of the use of resource potential in a particular region, the dynamics of relevant indicators was analyzed on the example of agricultural enterprises of Cherkassy region. The dynamics of resource potential of agricultural enterprises of Cherkassy region is analyzed. It is proved that the current state of equalization of the use of resource potential by subjects of domestic agricultural business has fundamental differences, which are conditioned both by the peculiarities of the organization of production in the system of agrarian production and by the general tendencies of the development of the national economy. This, in particular, concerns the intensification of the competition for land resources, as well as the consequences of the globalization of the domestic economy, its openness to foreign producers. Under these conditions, a systematic approach is needed to develop the directions of ensuring the competitive functioning of the subjects of agrarian entrepreneurship. The necessity of carrying out the corresponding state policy directed on increase of competitiveness of the domestic agrarian sector is substantiated.
Efficiency of the use of material technical resources – indispensable conditions of сompetitive management
Keywords: конкурентоспроможність; ресурсний потенціал; земельні ресурси; фермерські господарства; аграрне виробництво; competitiveness; resource potential; land resources; farm-farming; agrarian production